Heterogeneity of Human Pancreatic Islet Isolation Around Europe: Results of a Survey Study - Nano, Rita; Kerr-Conte, Julie A; Scholz, Hanne; Engelse, Marten; Karlsson, Marie; Saudek, Frantisek; Bosco, Domenico; Antonioli, Barbara; Bertuzzi, Federico; Johnson, Paul R V; Ludwing, Barbara; Ling, Zhidong; et al. (Transplantation, 2020)
BACKGROUND: Europe is currently the most active region in the field of pancreatic islet transplantation, and many of the leading groups are actually achieving similar good outcomes. Further collaborative advances in the field require the standardization of islet cell product isolation processes, and this work aimed to identify differences in the human pancreatic islet isolation processes within European countries. METHODS: A web-based questionnaire about critical steps, including donor selection, pancreas processing, pancreas perfusion and digestion, islet counting and culture, islet quality evaluation, microbiological evaluation, and release criteria of the product, was completed by isolation facilities participating at the Ninth International European Pancreas and Islet Transplant Association (EPITA) Workshop on Islet-Beta Cell Replacement in Milan. RESULTS: Eleven islet isolation facilities completed the questionnaire. The facilities reported 445 and 53 islet isolations per year over the last 3 years from deceased organ donors and pancreatectomized patients, respectively. This activity resulted in 120 and 40 infusions per year in allograft and autograft recipients, respectively. Differences among facilities emerged in donor selection (age, cold ischemia time, intensive care unit length, amylase concentration), pancreas procurement, isolation procedures (brand and concentration of collagenase, additive, maximum acceptable digestion time), quality evaluation, and release criteria for transplantation (glucose-stimulated insulin secretion tests, islet numbers, and purity). Moreover, even when a high concordance about the relevance of one parameter was evident, thresholds for the acceptance were different among facilities. CONCLUSIONS: The result highlighted the presence of a heterogeneity in the islet cell product process and product release criteria.
Keywords: Primary Cell Culture; Cold Ischemia; Surveys and Questionnaires; novorozenec; Infant, Newborn; Tissue and Organ Harvesting; Infant; Humans; Islets of Langerhans; kojenec; lidé středního věku; dítě; studená ischemie; Child; Aged; mladý dospělý; dospělí; věkové faktory; počet buněk; separace buněk; Islets of Langerhans Transplantation; senioři; lidé; Europe; výběr dárců; Cells, Cultured; časové faktory; průzkumy a dotazníky; Perfusion; odběr tkání a orgánů; předškolní dítě; Adult; primární buněčná kultura; transplantace Langerhansových ostrůvků; Practice Guidelines as Topic; Middle Aged; kultivované buňky; perfuze; Adolescent; Donor Selection; směrnice pro lékařskou praxi jako téma; Cell Separation; Young Adult; Langerhansovy ostrůvky; Age Factors; Child, Preschool; Time Factors; Evropa; Cell Count; mladiství